Expert model of the most important methodical exercises for fast skiing turns teaching - Danijela Kuna; Sanjin Džajić; Marko Mastelić (Exercise and Quality of Life)
The purpose of this research was to establish the expert model of learning and evaluation the most important methodical exercises for teaching short skiing turns in advanced skiing school. Participants were 20 skiing experts from different states. After the experts model was established, experts selected 5 most important methodical exercises for teaching short skiing turns. According to with the goal of the research, total frequency sum of expert choice of the most important methodical exercises has been used (O-observed; E-expected), while the difference between frequencies of expert evaluation has been tested by non-parametric Chi-square test (χ²) and statistic meaning of differences (p). By natural selection, the ranking was made, and selection of the most important methodical exercises for teaching short skiing turns. After data processing, statistical differences were significant in frequencies in which experts choose most important methodical exercises (c2=17.30; p=0.14) while the differences between the values of most important methodical exercises were not established (c2=2.15; p=0.91). Statistical differences based on nationality were not established. Based on the obtained results it can be concluded that the experts in spite of the structural differences and specificity within each ski schools are equally recognized and valued those most important methodical exercises who contain the basic characteristics of effective lessons. This research is a foundation for future modeling which has made a selection of significant errors and exercises for their elimination, and their hierarchical classification.